Whole-Body Bone Scan for Detecting Bone Metastasis in the Prostate-Specific Membrane Antigen Positron Emission Tomography Era: A Retrospective Cohort Study of Post-Radical Prostatectomy Prostate Cancer Patients - Chanikarn Poenateetai; Achiraya Teyateeti; Pawana Pusuwan; Ajalaya Teyateeti (Asia Oceania Journal of Nuclear Medicine and Biology)
Objective(s): To determine the detection rate of bone metastasis on bone scan of prostate cancer patients with rising serum prostate-specific antigen (PSA) following radical prostatectomy (RP) and to identify the predictive factors associated with bone metastasis. Methods: A study was conducted in 120 patients with rising serum PSA after RP. The data collected were pre and post-RP clinical parameters, including a trigger PSA (tPSA) level that prompted the treating physician to request a bone scan and PSA doubling time (PSADT). Bone scans were classified as positive or negative in conjunction with follow-up imaging and clinical information. Results: Of 120 bone scans, 6 (5%) were positive and 114 (95%) were negative for bone metastasis. In the median tPSA ranges of <0.5, 0.5-1.0, and >1.0 ng/mL, scan positivity was 2.1%, 6.3%, and 30%, respectively. Patients with positive scans showed higher tPSA (1.228 vs 0.256 ng/mL; p=0.003) and shorter PSADT (3.5 vs 12.2 months; p=0.005) than those with negative scans. The most significant predictors of a positive bone scan were tPSA (>1 vs ≤1 ng/mL; OR 15.286, 95% CI 2.594-90.064, p=0.003) and PSADT (<6 vs ≥6 months; OR 17.333, 95% CI 1.618-185.646, p=0.018). Conclusion: The detection rate of bone metastasis on bone scans in post-RP recurrent prostate cancer patients is only 5%, but the probability is much higher with tPSA >1 ng/mL and PSADT <6 months. Given its wide accessibility in Thailand, a bone scan should remain the preferred screening test for bone metastasis, with expected positive results in patients with high or rapidly rising PSA levels.